(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article explores the role of phraseological expressions in the Spanish language as carriers of national and cultural identity. Through the lens of linguistic relativity and cultural linguistics, it investigates how idioms, collocations, and proverbs reflect the historical experiences, cognitive patterns, and value systems of Spanish-speaking societies. Particular attention is given to the metaphorical structure, emotional expressiveness, and pragmatic functions of phraseological units. The study also examines the challenges involved in interpreting and teaching idioms across cultural boundaries. By analyzing authentic phraseological data from literature, media, and everyday speech, the article emphasizes the significance of phraseology in forming communicative competence and understanding the Spanish worldview.